2014
DOI: 10.1186/1471-2407-14-912
|View full text |Cite
|
Sign up to set email alerts
|

A case–control study of pre-operative levels of serum neutrophil gelatinase-associated lipocalin and other potential inflammatory markers in colorectal cancer

Abstract: BackgroundChronic inflammation is a key feature of colorectal cancer (CRC), meaning that inflammatory biomarkers may be useful for its diagnosis. In particular, high neutrophil gelatinase-associated lipocalin (NGAL) expression has been reported in CRC. Thus, we investigated whether serum NGAL and NGAL/MMP-9 could be potential biomarkers for the early detection of CRC. Concurrently, we studied other inflammatory biomarkers such as soluble tumor necrosis factor receptor 1 and 2 (sTNFR-1, sTNFR-2), and C reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 50 publications
0
22
1
Order By: Relevance
“…However, these relationships would need to be confirmed in a more extensive study of a larger cohort of healthy non‐smokers and smokers. In healthy adults, serum NGAL is correlated with age , but serum MMP‐9 may not be . In the present study, age‐corrected serum levels of MMP‐9 and proMMP‐9/NGAL were correlated with smoking status in patients with COPD but not in healthy smokers.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…However, these relationships would need to be confirmed in a more extensive study of a larger cohort of healthy non‐smokers and smokers. In healthy adults, serum NGAL is correlated with age , but serum MMP‐9 may not be . In the present study, age‐corrected serum levels of MMP‐9 and proMMP‐9/NGAL were correlated with smoking status in patients with COPD but not in healthy smokers.…”
Section: Discussioncontrasting
confidence: 46%
“…However, these relationships would need to be confirmed in a more extensive study of a larger cohort of healthy non-smokers and smokers. In healthy adults, serum NGAL is correlated with age [58,59], but serum MMP-9 may not be [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…A case-control study reported higher levels of serum sTNFR2 in CRC cases than patients with benign disorders. 34 Prospective studies have had mixed results, with one study reporting a positive association with high levels and protection by aspirin/NSAID use that was restricted to individuals with high levels, 35 while two other studies were null. 36,37 BMI is a recognized risk factor for CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Many transcription factors, including the estrogen and androgen receptors, regulate NGAL expression by both positive and negative mechanisms [67][68][69][70][71][72][73][74][75][76][77]. 11 NGAL is an important molecule in many different types of cancer including: breast [9,10,77], colorectal (CRC) [78,79], endometrial [80], esophageal [7,81], gastric cancer [6], liver [82][83][84], lung [85][86][87] ovarian [88], pancreatic [89,90], prostate [76,91], renal [8,92] and thyroid cancer [68]. In general, elevated NGAL expression has been associated with advanced cancer and poor prognosis.…”
Section: Accepted Manuscriptmentioning
confidence: 99%